Project management a systems approach to planning, scheduling, and controlling - Kerzner, Harold (Wiley, 2017)
Project Management, or the "Project Management bible" as it's widely known, provides practical guidance on all aspects of project management. It features a streamlined approach to PM functions-in full alignment with the concepts and standards outlined in PMI's latest A Guide to the Project Management Body of Knowledge, (PMBOK® Guide)-without stinting on detailed coverage of the tools and methods used at all stages of a project. This 12th Edition has been updated to reflect recent changes to the PMBOK® Guide-Sixth Edition, and features in-depth coverage of emerging topics, including global stakeholder management, causes of failure, agile project management, project governance failure, customer approval milestones, classifying project metrics, and more. Also, supplementary materials are available for students, professionals, and instructors.